Marriage and Union Formation in the United States: Recent Trends Across Racial Groups and Economic Backgrounds. - Bloome, Deirdre; Ang, Shannon (Demography (Springer Nature), 2020)
Family formation in the United States has changed dramatically: marriage has become less common, nonmarital cohabitation has become more common, and racial and economic inequalities in these experiences have increased. We provide insights into recent U.S. trends by presenting cohort estimates for people born between 1970 and 1997, who began forming unions between 1985 and 2015. Using Panel Study of Income Dynamics data, we find that typical ages at marriage and union formation increased faster across these recent cohorts than across cohorts born between 1940 and 1969. As fewer people married at young ages, more cohabited, but the substitution was incomplete. We project steep declines in the probability of ever marrying, declines that are larger among Black people than White people. We provide novel information on the intergenerational nature of family inequalities by measuring parental income, wealth, education, and occupational prestige. Marriage declines are particularly steep among people from low-income backgrounds. Black people are overrepresented in this low-income group because of discrimination and opportunity denial. However, marriage declines are larger among Black people than White people across parental incomes. Further, most racial differences in marriage occur among people from similar socioeconomic backgrounds. Family inequalities increasingly reflect both economic inequalities and broader racial inequalities generated by racist structures; in turn, family inequalities may prolong these other inequalities across generations.